(untitled) (Revista Lusófona de Educação, 2025)
This article analyzes the relationship between musical experiences and the well-being of children participating in the Children’s Choir of Casa da Música, in Porto. Well-being is a subjective concept that integrates various areas of life, being associated with the feeling of personal satisfaction. Research indicates that music promotes the expression of feelings and emotional strengthening, with a significant role in children’s well-being. Through the ethnographic method, participant observation, focus group discussions with choir members, and interviews with trainers and parents were conducted. The results indicate that musical practice in the context of the Choir enhances well-being, fostering positive feelings such as happiness and life satisfaction. It is concluded that music and singing not only enhance artistic skills but are also important educational tools, promoting the personal, social, and emotional development of the participants.